Manipulationstechniken - Edmüller, Andreas,Wilhelm, Thomas (Haufe Group, 2020)
Warum habe ich bloß
Keywords: Wirtschaft: Sachbuch; Ratgeber; Psychologie: Sachbuch; Ratgeber; Literatur für Manager; Hardcover; Softcover / Sachbücher/Angewandte Psychologie; überzeugen; Manipulationstechniken; durchsetzen; verhandeln; Abwehrstrategien; ebook; EPUB; epdf; e-book; e-pub; e-pdf; Manipulation; Gesprächsführung